The New Social Learning: A Guide to Transforming Organizations Through Social Media - Nacer Aounallah (Journal of Applied Communications, 2014)
When it comes to social media, several perspectives are prevalent among those who have knowledge of the subject. Unfortunately, prior to quite recently, I would have been classified as one of those who view the phenomenon as an entertainment tool riddled with trivial information. Thankfully, this book has contributed to rectifying many preconceived misconceptions and expanded upon potential avenues of basic communication by both showcasing applications of successful utilization and introducing technologies that might not necessarily be at the forefront of applied communication.
Keywords: Media; Education; Micro Sharing; Misconception; book review